Studies on the text of the New Testament and early Christianity : essays in honour of Michael W. Holmes on the occasion of his 65th birthday - Holmes, Michael W. 1950-; Gurtner, Daniel M.; Hernández, Juan, 1968-; Foster, Paul, 1966- (New Testament Tools, Studies and Documents, 2015)
The collection of essays focuses on the twin areas of research undertaken by Prof. Michael W. Holmes. These are the sub-disciplines of textual criticism and the study of the Apostolic Fathers. The first part of the volume on textual criticism focuses on issues of method, the praxis of editing and collating texts, and discussions pertaining to individual variants. The second part of the volume assembles essays on the Apostolic Fathers. There is a particular focus on the person and writings of Polycarp, since this is the area of research where Prof. Holmes has worked most intensively.